The Tsinghua University-Ma Huateng Telescopes for Survey: Overview and Performance of the System. (29th October 2020) - Zhang, Ji-Cheng; Wang, Xiao-Feng; Mo, Jun; Xi, Gao-Bo; Lin, Jie; Jiang, Xiao-Jun; Zhang, Xiao-Ming; Li, Wen-Xiong; Yan, Sheng-Yu; Chen, Zhi-Hao; Hu, Lei; Li, Xue; et al.
Abstract: Over the past decade, time-domain astronomy in optical bands has developed rapidly with the operations of some wide-field survey facilities. However, most of these surveys are conducted with only a single band, and simultaneous color information is usually unavailable for the objects monitored during the survey. Here we present introductions to the system of Tsinghua University-Ma Huateng Telescopes for Survey (TMTS), which consists of an array of four optical telescopes installed on a single equatorial mount. Such a system is designed to get multiband photometry simultaneously for stars and transients discovered during the survey. The optics of each telescope is a modified Hamilton-Newtonian system, covering the wavelengths from 400 to 900 nm, with a field of view (FoV) of about 4.5 deg 2 and a plate scale of 1.″86 pixel −1 when combining with a 4 K  × 4 K QHY4040 CMOS detector. The TMTS system can have a FoV of about 9 deg 2 when monitoring the sky with two bands (i.e., SDSS g and r filters) at the same time, and a maximum FoV of ∼18 deg 2 when four telescopes monitor different sky areas in monochromatic filter mode. For an exposure time of 60 s, the average 3 σ detection limit of the TMTS system can reach at ∼19.4 mag in Luminous filter and at ∼18.7 mag in SDSS r filter. The preliminary discovery obtained during the first few months' survey is briefly discussed. As this telescope array is located at the Xinglong Observatory of NAOC, it can have an excellent synergy with the spectroscopic survey by the LAMOST (with a FoV of about 20 deg 2 ) at the same site, which will benefit the studies of stellar and binary physics besides the transient sciences.